2020
DOI: 10.3390/ijerph17030763
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Suboptimal Health Status and the Relationships between Suboptimal Health Status and Lifestyle Factors among Chinese Adults Using a Multi-Level Generalized Estimating Equation Model

Abstract: This study examined the prevalence of suboptimal health among Chinese adults based on a large-scale national survey and clarified the relationship between suboptimal health and lifestyle factors. We used multi-level generalized estimating equation models to examine the relationships between suboptimal health and lifestyle factors. Of the 48,978 respondents, 34,021 reported one or more suboptimal health symptoms, giving a suboptimal health status prevalence of 69.46%. After controlling for the cluster effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 30 publications
3
32
0
Order By: Relevance
“…Several studies also found that many lifestyle factors were closely associated with SHS among adults [5,29,30,35]. In our previous study, unhealthy lifestyles were found closely associated with SHS among adults aged above 18 years old, including smoking, drinking alcohol, short sleep duration, poor sleep quality, lack of regular exercise, stress, negative life events, unhealthy diet choices, and irregular meal times [7]. In this study, we found that these lifestyle factors were also closely associated with SHS among children aged 10-17 years old.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Several studies also found that many lifestyle factors were closely associated with SHS among adults [5,29,30,35]. In our previous study, unhealthy lifestyles were found closely associated with SHS among adults aged above 18 years old, including smoking, drinking alcohol, short sleep duration, poor sleep quality, lack of regular exercise, stress, negative life events, unhealthy diet choices, and irregular meal times [7]. In this study, we found that these lifestyle factors were also closely associated with SHS among children aged 10-17 years old.…”
Section: Discussionmentioning
confidence: 75%
“…In 2007-2011, we conducted a national survey in six provinces or autonomous regions of China to examine SHS among Chinese adults and children across a broad age range and covering dozens of ethnic minorities. And we found that the prevalence of SHS was 69.46% among Chinese adults and the prevalence for male adults (67.74%) was lower than that for female adults (72.67%) [7].…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…Irregular meal time indicated the participant could not have breakfast, lunch and dinner at xed time period. Sub-health status was assessed with the Delphi sub-health scale [19,20].…”
Section: De Nitiona Of Depression and Covariatesmentioning
confidence: 99%
“…SHS is becoming a global health issue. The SHS prevalence took up 71.7% in nurses [8], 69.46% in Chinese adults [9] and 55.9% in Chinese students [10], and SHS had adverse effects on metabolic syndrome [3], cognitive impairment [7], oxidative stress in pregnant women [2]. Thus, it might be of great importance for medicine staff to early detect and prevent SHS resulting in chronic disease and other adverse impacts.…”
Section: Introductionmentioning
confidence: 99%